Compression of computer-generated holograms in image projection - Kochańska, Paula Adrianna; Makowski, Michal (Photonics Letters of Poland, 2017)
Computer-generated holography is a technique of a lossless and lens-less forming of images. Methods that use local devices to compute such holograms are very power- and time-consuming. In order to make it possible to transfer the calculations to the cloud, it is necessary to elaborate efficient algorithms of a lossless compression. In this paper two methods of compression are presented and supported by both simulation and experimental results. A lossy compression method omitting certain bit-planes of the holographic data is also presented, which allows insignificant loss of information, while achieving a greater compression ratio. Full Text: PDF References M. Makowski "Simple holographic projection in color.", Opt. Express 20, 25130-25136 (2012). CrossRef M. Makowski, I. Ducin, K. Kakarenko, J. Suszek, A. Kowalczyk, "Performance of the 4k phase-only spatial light modulator in image projection by computer-generated holography, " Phot. Lett. Poland 8, 26-28 (2016). CrossRef A. Kowalczyk, M. Bieda, M. Makowski, I. Ducin, K. Kakarenko, J. Suszek, A. Sobczyk, "Analysis of computational complexity in holographic lens-less projection," Phot. Lett. Poland 6, 84-86 (2014). CrossRef M. Makowski, "Minimized speckle noise in lens-less holographic projection by pixel separation," Opt. Express 21, 29205-29216 (2013). CrossRef H. Niwase, N. Takada, H. Araki, Y. Maeda, M. Fujiwara, H. Nakayama, T. Kakue, T. Shimobaba, T. Ito "Real-time electroholography using a multiple-graphics processing unit cluster system with a single spatial light modulator and the InfiniBand network." Opt. Eng. 55, 093108-093108 (2016). CrossRef T. Shimobaba and T. Ito, "Random phase-free computer-generated hologram", Opt. Express 23(7) 9549-9554 (2015) CrossRef S.R. Kodituwakku, "Comparison of lossless data compression algorithms for text data", Indian Journal of Computer Science and Engineering Vol 1 No 4 416-426 (2010) DirectLink